Collaborative tools in the primary classroom: Teachers' thoughts on wikis - Agesilaou, Andria; Vassiliou, Christiana; Irakleous, Sotiroula; Zenios, Maria (My University, 2014)
The purpose of this work-in-progress study is to examine the attitudes of primary school teachers in Cyprus on the use of wikis as a mean to promote collaborative learning in the classroom. A survey investigation was undertaken using 20 questionnaires and 3 semi-structured interviews. The survey results indicate a positive attitude of teachers in Cyprus to integrate wikis in primary education for the promotion of cooperation. As such collaborative learning activities among pupils are being encouraged.
Keywords: Collaboration; Collaborative learning; Educators; Primary education; Wikis